Social design, innovation and ergonomics: Reflections on education, transdisciplinarity and new blurred models for sustainable social change - Ferreira, Ana Margarida; Souleles, Nicos; Savva, Stefania (My University, 2019)
Social innovation is not a new fact, but it has grown in importance over the last years as a driver for social change [1]. Although there is no universal definition of it, one widely-used is ‘ideas that are social in their ends and in their means’ [2] and concerns the process of developing and deploying new solutions to often systemic and complex social and environmental issues. On the other hand, social art is seen as any artistic expression that aims at inspiring social impact and change effectively society through emotionally captivating experiences [3]. Also, social ergonomics is understood as responses to social aspects of system use, envisioning, among others, socially proactive design and discussing the possibilities for embedding new paradigms for communication and problem-solving in specialized information systems [4]. Based on these ideas, this paper will elaborate on the above concepts, confronting and correlating them as complementary human actions and domains. Some considerations and challenges on the theme, as outputs of a post-doc research, will be also offered. It will be shown transdisciplinary approaches, methods, social actors, and complementary and blurred practices to an effective and meaningful design and implementation of new products, services, and systems. Its social, cultural and, educational relevance or holistic understanding will be underlined as strategies to achieve the sustainability of social systems, to share social value and promote resilience and wellbeing in a highly complex and changing world.
Keywords: Collaborative learning; Holistic approach; Social change; Social design; Social innovation; Sustainability; Systemic drivers; Transdisciplinarity